1996
DOI: 10.1121/1.414662
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic scattering in the ocean from velocity and density fluctuations in the sediments

Abstract: According to spectral analyses of many crosswell acoustic tomograms and cores collected from ten seabed locations ͓Yamamoto, J. Acoust. Soc. Am. 98, 2235-2248 ͑1995͔͒, the 3-D power spectra of velocity and density fluctuations in the seabed sediments are strongly anisotropic and dipping in general. Anisotropy, dip, and spectral properties of the fluctuations vary greatly depending on the sediment type and the geographical location. Based on the Born approximation and the Wood sediment model, an analytical solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Traditionally, Gaussian and exponential correlation functions have often been used because of their mathematical simplicity (14,33,35]. Recently, a power-law type of correlation function has attracted more interest [53,63]. Meanwhile, Yamamoto, in his measurement of velocity variability using crosswell acoustic tomography, found the measured power spectra approximate a power law [64].…”
Section: Correlation Functions Of Sound Speed Variationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, Gaussian and exponential correlation functions have often been used because of their mathematical simplicity (14,33,35]. Recently, a power-law type of correlation function has attracted more interest [53,63]. Meanwhile, Yamamoto, in his measurement of velocity variability using crosswell acoustic tomography, found the measured power spectra approximate a power law [64].…”
Section: Correlation Functions Of Sound Speed Variationsmentioning
confidence: 99%
“…Recently, Yamamoto [39] used the same approach as Chernov's [33) to model density and sound speed fluctuations in the sediment. The above fluctuations were described by a power law distribution and the parameters were estimated from crosswen tomography.…”
Section: Morse and Ingardmentioning
confidence: 99%
See 1 more Smart Citation
“…The work of many researchers has shown that this expression for bottom scattering strength is of the wrong form for small grazing angles for ocean sediments with a sound speed ratio close to or less than one (Holland, 1996). The effect of scattering from the sub-bottom volume of the sediment and from sub-bottom scattering horizons was noted in the results of the CST program and has been included in the modeling work by many researchers over the past 10 years (Mourad, 1993;Yamamoto, 1996;Holland, 1998). ) (Gauss, 2000).…”
Section: Aspm (Acoustic System Performance Model)mentioning
confidence: 99%
“…The preferential alignments in the Earth ranging from mineral orientations, grain, or micro cracks to regional fractures result in the seismic anisotropy (Crampin, 1994). According to spectral analysis of many cross-well acoustic tomograms and cores collected from seabed locations, the 3-D power spectra of velocity and density fluctuations in the seabed sediments are strongly anisotropic and dipping in general (Yamamoto, 1996). Gurevich (2003) investigated that elastic properties of fluid-saturated porous rocks with aligned fractures can be studied using the model of fractures as linear slip interfaces in an isotropic porous background.…”
Section: Introductionmentioning
confidence: 99%